The Impact of Social Media Marketing, Brand Image, Product Quality, on Purchasing Decision for Somethinc Cushion: (Study On The Faculty Of Economics & Business, Dian Nuswantoro University) - Keisha Serafina; Diana Aqmala; Pradana Kusuma Jati (International Journal of Economics, Management and Accounting, 2024)
This study aims to determine the effect of: (1) Social Media Marketing on Purchasing Decisions for UDINUS FEB Students, (2) Brand Image on Purchasing Decisions for UDINUS FEB Students, (3) Product Quality on Purchasing Decisions for UDINUS FEB Students. This research includes survey research. The population of this study were students of the Faculty of Economics and Business, Dian Nuswantoro University with a total of 160 respondents. Sampling using Non Probability Sampling with purposive sampling technique. The research data collection technique was carried out through an online Google Form questionnaire. The results showed that the Social Media Marketing had a positive and significant effect on purchasing decisions with a significant value of 5.104 > 1.655, Brand Image had a positive and significant effect on purchasing decisions with a significant value of 3.207 > 1.655, and Product Quality had a positive and significant effect on purchasing decisions with a significant value of 2.930 > 1.655 on Somethinc Cushion  on Students of the Faculty of Economics and Business, Dian Nuswantoro University.